МОДЕЛЮВАННЯ НАГРІВАННЯ МЕТАЛЕВОГО РОЗПЛАВУ У ВІДБИВНІЙ ПЕЧІ ПРИ ЕЛЕКТРОМАГНІТНОМУ ПЕРЕМІШУВАННІ - Глухенький, О.І.; Гориславець, Ю.М.; Бондар, О.І. (Інститут електродинаміки НАН України, Київ, 2015)
The multiphysical numerical threedimentional modelling and research of time dependent heating of the melt in the reverberatory furnace during it electromagnetic stirring by means of combined inductor, which is capable separately to create travelling or pulsating magnetic fields with multiphase or single phase power supply respectively has been done. Electromagnetic, hydrodynamic and heat processes were considered as weakly bound, that allowed to solve appropriate problems consistently. Electromagnetic problem was calculated relative to the magnetic vector and electric scalar potentials, resulting in distribution volume received electromagnetic forces that cause movement of liquid metal. Calculation of nonstationary motion of liquid metal in the furnace bath was carried out by solving nonlinear Navier-Stokes equations using k-ε turbulence model. Temperature distribution of metal in the furnace bath during its heating was found considering the velocity field which were obtained by determining the movement of liquid metal. Analysis of the obtained data showed that significantly reduce overheating on metal surfaces can be achieved by shifting down a combined stirrer relatively symmetrical position on height and using alternate action of and pulsating magnetic fields with switching period, which is approximately equal to the duration of the transition hydrodynamic process. References 9, figures 5, tables 2.